Damnable Lives? The Inter-Textual Relations between Marlowe’s “Doctor Faustus” and “The English Faust” Book - Kojoyan, Ani (Armenian Folia Anglistika, 2014)
Christopher Marlowe’s play Doctor Faustus is a problematic work in regards to the issues of its date and authorship, but one thing can be stated with certainty: it was inspired by The History of the Damnable Life and Deserved Death of Doctor John Faustus which is commonly known as the English Faust Book. The present article observes inter-textual dimensions between Marlowe’s tragedy Doctor Faustus and its prose source-book – the English Faust Book. The article discusses intertextual relations both at paradigmatic and syntagmatic levels. According to the analysis, it becomes obvious that despite several similarities between the two texts, certain differences also exist which are conditioned by political and religious factors of time and social-historical factors of space.
Keywords: Christopher Marlowe; Early Modern English Drama; History and Religion; British Studies; text interpretation; intertextuality